Experimental duration determines the effect of arbuscular mycorrhizal fungi on plant biomass in pot experiments: A meta-analysis - Qin, Mingsen; Li, Lei; Miranda, Jean‐Pascal; Tang, Yun; Song, Bo; Oosthuizen, Maria Kathleen; Wei, Wangrong (Frontiers in Plant Science, 2022)
Arbuscular mycorrhizal fungi (AMF) play various important roles in promoting plant growth. Numerous environmental and evolutionary factors influence the response of plant growth to AMF. However, the importance of each individual factor on the effects of AMF on plant biomass is not clearly understood. In this study, a meta-analysis using 1640 observations from 639 published articles related to the influence of AMF on the plant shoot, root, and total biomass was performed, and the importance of 13 different experimental setting factors impacting on the influences were quantitatively synthesized. The meta-analysis showed that AMF had positive effects on plant shoot, root, and total biomass; and that experimental duration, plant root-shoot ratio, AMF root length colonization, plant family, pot size, soil texture, and soil pH all influenced the effect of AMF on the shoot, root, and total biomass. In addition, plant root system and plant functional types had impacts on the effect of AMF on shoot biomass; AMF guild had impacts on the effect of AMF on root biomass. Among these factors, experimental duration, plant root-shoot ratio, and pot size were the most important three factors to predict the AMF effect on plant shoot, root, and total biomass. This study comprehensively assesses the importance of different factors that influence the response of plant to AMF, highlighting that the experimental duration, plant root-shoot ratio, and pot size should be considered for pot experiment in AMF function researching. The inclusion of multiple unfavorable factors which may obscure or confound the observed function of AMF should be avoided.